Maju Kraf Enterprise / Adil Fikri Jumiry...[et.al] - Farizan, Fauzan Harith Izat; Hassan, Mohammad Syazrul Syahril; Abdul Fataf, Mohammad Arif (Faculty of Plantation and Agrotechnology, 2017)
To better understand the purpose of the business and act as guideline to manage the business effectively and efficiently, Business plan enables the entrepreneur to evaluate new product line and services, promotion, or expansion. Besides that, business plan consists of theory part of each aspect that we need to master in order to make the venture is profitable. In making the plan become real, plan and strategies are needed as guideline in making any decision that can affect the business development from time to time. In Maju Kraf Enterprise, we see the business plan as primary resource for us in doing the entire task that occurs in our company.